Strategi Pelayanan Prima Pada Program "Motor Pintar" Dinas Perpustakaan Dan Kearsipan Kabupaten Sidoarjo - Aditya, Muhammad Rafli; Pratama, Ananta (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
The smart motorcycle program is an innovation in mobile library services launched by the Sidoarjo Regency Library and Archives Office to increase people's access to literacy, especially in remote areas. This study aims to analyze the strategy of implementing excellent service in the program, which includes understanding the needs of the community, providing relevant book collections, and improving the quality of officer services. The research uses a qualitative descriptive method with data collected through interviews and literature studies. The results of the study show that this program has succeeded in increasing public participation in library services, although it still faces obstacles such as limited collections, facilities, labor, and inflexible service hours. The recommendations given include adding book collections, improving facilities and infrastructure, and adjusting service operating hours. With these improvements, This program has great potential in increasing people's interest in reading and literacy in a sustainable manner.